Computational prediction and development of a thermostable endoglucanase I from Fusarium oxysporum - Noorbatcha, Ibrahim Ali; Ahmad, Abdul Aziz; Mohd. Salleh, Hamzah (2014)
Cellulose is the most abundant biopolymer on earth. Enzymatic degradation of this biopolymer is a crucial step toward its conversion to bioethanol. However the current cellulosic enzymes are unable to withstand high temperature of industrial processes. In this work we use computer simulations to predict thermostable endoglucanase. The molecular dynamics simulation is a powerful tool that can be used to study the enzymes behaviour at high temperature. On the basis of computer simulations we have predicted a mutant endoglucanase with improved thermal stability properties.